Mayaderm - Dixit, Mukund R. ([London] : SAGE, 2016)
This case describes the journey of a doctor from curiosity to product formulation to enterprise promotion and presents the problems faced by him in succeeding commercially. The innovator perceives the innovation to be a medical success and a commercial non-starter. The case provides an opportunity to evaluate the efforts of Dr Shah and propose a strategy for the future.
Originally Published in: Dixit, M. R. (2015). Mayaderm. BP0385. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; New products -- Case studies; Creative ability in business -- Case studies; Drug development -- Case studies